Rituximab efficacy in pediatric patients with refractory nephrotic syndrome - Alaifan, Badr A.; Jamjoom, Ahmed A.; Jamal Aldeen, Raghad I.; Hariri, Mohammad F.; Hakim, Raghad F.; Dhahri, Falih A.; Murad, Weam A.; Aletani, Lujain F.; Bafail, Abrar A.; Raml, Enas; El Desoki, Sherif M.; Safdar, Osama Y. (International Journal of Research in Medical Sciences, 2017)
Background: Nephrotic syndrome (NS) in children is a disease of glomerular filtration barrier failure, manifesting with severe proteinuria leading to hypoalbuminemia, hypercholesterolemia, and generalized edema. it could be primary or secondary. In primary NS, also known as idiopathic NS, the histological findings of Primary NS include minimal change disease which mainly respond to steroids (steroid sensitive NS), focal segmental glomerulosclerosis which are usually steroid resistant or membranous nephropathy. Rituximab has been shown to be effective for patients with complicated FRNS/SDNS and refractory SRNS. While the incidence of nephrotic syndrome (NS) is increasing, the morbidity of difficult-to-treat NS is significant. Methods: This is a retrospective cohort study that took place in King Abdulaziz University Hospital from 2012 to 2016. Patients included: Any patient under 18 years, and diagnosed with steroid resistant and dependent nephrotic syndrome. Patients excluded: Any patient above 18 years, and known to have secondary Nephrotic Syndrome. Results: Present study consists of 24 children with nephrotic syndrome (NS) were recruited in the study. In the population 8 patients (33.33 %) were diagnosed with SDNS, while the other 16 patients (66.67%) were diagnosed SRNS. Also, patients who were treated with Rituximab we found that (the mean) number of relapses per year before rituximab was about 2.67±1.49 (standard deviation 1.49), while patient who relapsed after rituximab was about 1.09±1.38 (standard deviation 1.38). Conclusions: Rituximab is a biological agent that started to be widely used in difficult nephrotic syndrome cases. The effectiveness of rituximab is most observed in steroid depended nephrotic syndrome patients since it decreases the frequency of relapses and steroid dependency. However, it has been shown that it is less effective in steroid resistant nephrotic syndrome cases and was associated with significant numbers of relapses.